2017
DOI: 10.4103/ijccm.ijccm_64_16
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of venous to arterial carbon dioxide difference during early resuscitation in critically ill patients with septic shock

Abstract: Context:The partial pressure of venous to arterial carbon dioxide gradient (PCO2 gap) is considered as an alternative marker of tissue hypoperfusion and has been used to guide treatment for shock.Aims:The aim of this study was to investigate the prognostic value of venous-to-arterial carbon dioxide difference during early resuscitation of patients with septic shock and compared it with that of lactate clearance and Acute Physiology and Chronic Health Evaluation II (APACHE-II) score.Settings and Design:Forty pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Se han realizado múltiples estudios científicos internacionales donde el DCO 2 mayor de 6 mmHg se asoció a mayor mortalidad e hipoperfusión. 32 Estos hallazgos podrían ser resultado de la alteración del flujo sanguíneo secundario a una disminución del GC o alteración de la microcirculación, 33 como consecuencia, los tejidos recibirán menor perfusión y se mantendrán hipoxémicos. 34 Debido a que en nuestra población no fue posible el monitoreo invasivo del GC, éste se calculó de forma no invasiva (fórmula de Fick) y se observó una media de 8.2L/min, sin presentar diferencia entre ambos grupos; sin embargo, los pacientes con DCO 2 menor de 6 mmHg desarrollaron mayor número de casos de LRA.…”
Section: Discussionunclassified
“…Se han realizado múltiples estudios científicos internacionales donde el DCO 2 mayor de 6 mmHg se asoció a mayor mortalidad e hipoperfusión. 32 Estos hallazgos podrían ser resultado de la alteración del flujo sanguíneo secundario a una disminución del GC o alteración de la microcirculación, 33 como consecuencia, los tejidos recibirán menor perfusión y se mantendrán hipoxémicos. 34 Debido a que en nuestra población no fue posible el monitoreo invasivo del GC, éste se calculó de forma no invasiva (fórmula de Fick) y se observó una media de 8.2L/min, sin presentar diferencia entre ambos grupos; sin embargo, los pacientes con DCO 2 menor de 6 mmHg desarrollaron mayor número de casos de LRA.…”
Section: Discussionunclassified
“…Our study also showed similar results with (5.70 + 1.29 mmol/l.vs 9.09+1.58mmo/l at T6, 3.9+1.18mmol/l. vs 8.94+1.34mmo/l at T12 and 2.45+1.09 mmol/l.vs 8.79+1.33mmo/l in survivors and nonsurvivors with p<0.0001 Mahajan RK et al 16 studied patterns of scvo2 lactate and (v-a)co2 difference in the prognosis of septic shock patients and concluded that in septic patients, baseline vaCO 2 of ≤ 6 mmHg was associated with higher mortality, but only in those patients with ScvO 2 >70%. This was thought to be due to impaired mitochondrial respiration in sepsis with nonutilization of oxygen by the cell may decrease CO 2 production, since anaerobic metabolism is less efficient in producing CO 2.…”
Section: Figure 1 Tablementioning
confidence: 94%
“…Our study is in agreement with this study as the non-survivors had higher v-a co2difference (9.78+0.78 mm Hg) and non-survivors had lower v-a co2difference at T6 p<0.0001. In their study of prognostic value of venous-toarterial carbon dioxide difference during early resuscitation of patients with septic shock, Helmy TA et al 16 and compared venous-to-arterial carbon dioxide difference with that of lactate clearance and concluded that At T0, non survivors showed high PCO2 gap (8.37±1.36 mmHg) than survivors (7.55±0.95 mmHg) with (P=0.030). At T6, showed higher PCO2 gap (9.48±1.47 mmHg) with (P < 0.001) and higher mean lactate values (62.71±23.66 mg/dl) with statistically significant difference (P<0.001) than survivors where PCO2 gap and mean lactate values became much lower, 5.91±1.12 mmHg and 33.61±5.80 mg/dl, respectively.…”
Section: Figure 1 Tablementioning
confidence: 99%
“…Exactly 2 years ago, an article was published in Indian Journal of Critical Care Medicine, which showed that high PCO 2 gap after 6 hours of resuscitation of septic shock patients was associated with high mortality. 1 The study by Arajuo et al, that is being published in this issue of Indian Journal of Critical Care Medicine fails to show any such correlation. 2…”
Section: Introductionmentioning
confidence: 93%